PNEUMONIA AND MORTALITY RISK: STUDY ON DIABETIC AND NON-DIABETIC PATIENTS - MP, NARMADHA; JAYAN, NIKHNA; JOHNY, RON (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Pneumonia, a frequent coexistent of diabetes, is an important cause of morbidity and mortality in diabetes. The diabetic population is not only prone to pulmonary infection but it is also prone to different comorbidity and complication. Therefore, the aim of the study was to assess and compare mortality in diabetic pneumonia and non-diabetic pneumonia group. Methods: This was a prospective case–control study conducted in two hospitals which included 76 patients with Group 1 (patients with diabetics) and 70 patients with Group 2 (patients who are non-diabetics). Results: Among 146 patients, mortality in diabetics was 5.47% in comparison with non-diabetics 4.10%. Patients in the diabetic group were significantly (p=0.044) more among pneumonia severity index (PSI) Class IV–V (9.21%) than PSI Class I-III (1.31%). Most of the patients had predisposing condition or underlying disease, hypertension (87.50% vs. 50%), pulmonary (37.50% vs. 83.33%), neurological (37.50% vs. 83.33%), and renal disease (37.5% in diabetic). The common complication in both groups was pleural effusion (50%) and septic shock (25%). Gram-negative bacteria (62.5% vs. 33.33%) and drug-resistant pathogens score (87.5% vs. 66.66%) were more prevalent in both groups. Conclusion: Our study reveals that poor long-term glycemic control among patients with diabetes clearly increases the risk of hospitalization and mortality. In non-diabetic pneumonia patients, antibiotic-resistant bacteria and preexisting pulmonary disease act as a predictor for mortality.